Ezekiel - Tuell, Steven Shawn (New international biblical commentary / Old Testament series, 2009)
Introduction -- Ezekiel's message of judgment (Ezek. 1-33). Ezekiel's call (Ezek. 1-3) ; Signs and oracles of judgment (Ezek. 4-7) ; The glory departs (Ezek. 8-11) -- Laying the blame and taking responsibility (Ezek. 12-19) ; Signs, sayings, and oracles of judgment (Ezek. 12-14) ; Riddles and metaphors (Ezek. 15-17) ; Personal accountability (Ezek. 18-19) -- Oracles of destruction (Ezek. 20-24) ; An unholy history (Ezek. 20:1-44) ; Miscellaneous oracles of judgment (Ezek. 20:45-22:31) ; A tale of two sisters (Ezek. 23) ; Jerusalem's siege, in parable and sign (Ezek. 24) -- Oracles against the nations (Ezek. 25-32) ; Ammon, Moab, Edom, and Philistia (Ezek. 25) ; Tyre, Sidon--and Israel (Ezek. 26:1-28:26) ; Egypt (Ezek. 29:1-32:32) ; Endings and beginnings (Ezek. 33) -- Ezekiel's message of hope and restoration (Ezek. 34-48). Oracles of restoration (Ezek. 34-37) ; Gog of Magog (Ezek. 38-39) -- The law of the temple (Ezek. 40-48) ; Prologue to the law of the temple: the Lord comes home (Ezek. 40:1-43:9) The law of the temple (Ezek. 43:10-46:24) ; Epilogue to the law of the temple: river, land, city (Ezek. 47-48)